Ten new species of marine bryozoans (Gymnolaemata: Cheilostomatida) from Brazil - Almeida, Ana C.s.; Larré, Igor R.n.m.; Vieira, Leandro M. (Zootaxa, 2021)
Despite a recent increase in the number of taxonomic studies on the bryozoan fauna of northeastern Brazil, new discoveries and re-examination of museum specimens allow the continued recognition of new taxa. Here, we describe ten new cheilostome species from the northeastern continental shelf of Brazil based on different museum collections. The new species are: Thalamoporella tupinamba n. sp., Turbicellepora papula n. sp., Plesiocleidochasma brasiliensis n. sp., Plesiocleidochasma infundibulum n. sp., Rhynchozoon turgidum n. sp., Cribrilaria brasiliensis n. sp., Hippoporina titan n. sp., Crepidacantha fasciata n. sp., Crepidacantha browni n. sp., and Hippopodina inarmata n. sp. Some specimens previously reported from northeastern Brazil are here reassigned to the newly described taxa, and two new combinations, Cribrilaria caraguata (Winston & Vieira, 2013) n. comb. and Cribrilaria tuba (Winston & Vieira, 2013) n. comb., are proposed.